Characterizing Chronic Ischemic and Structural Brain Changes on CT Following Road Traffic Trauma in Tripoli, Libya - Ali Ramdan,; Sama Fadeel,; Aisha Dabnoun, (AlQalam Journal of Medical and Applied Sciences, 2025)
Traumatic brain injury (TBI) is a major cause of morbidity and mortality globally, particularly in low- and middle-income countries where road traffic accidents are prevalent. Early detection of intracranial lesions is crucial for optimizing management and preventing long-term neurological deficits. While MRI provides detailed imaging, CT remains the primary modality in emergency settings due to rapid acquisition and accessibility. Epidemiological data on CT-detected injury patterns in resource-limited settings are limited. To evaluate the prevalence, type, and distribution of CT-detected brain lesions among patients sustaining head trauma. A retrospective cross-sectional study was conducted on 90 patients with head trauma from road traffic accidents in Tripoli, Libya. Non-contrast CT scans were analyzed for lesion type, location, cerebral atrophy, ventricular enlargement, and MRI recommendations. Abnormal CT findings were observed in 66.7% of patients. Old ischemic infarctions predominated (83.3%), with right frontal and parietal lobes most affected. Ventricular enlargement and atrophy were present in 33.3% and 44.4% of cases, respectively. Chronic ischemic lesions were the most frequent abnormalities, emphasizing CT’s critical role in early trauma assessment and guiding follow-up strategies.